The Relationship Between the Application of Spiritual Care and Social Support with the Spirituality Level of Patients Confirmed Positive for Covid-19 - Marni Marni; Dewi Gayatri; Dhea Natashia; Wati Jumaiyah (Sekolah Tinggi Ilmu Kesehatan Kendal, 2022)
The COVID-19 pandemic has had a major impact on physical, economic, social and mental health so that it can affect the level of spirituality in humans. This study aims to determine the relationship between implementation and social support with spirituality levels in patients who are confirmed positive for Covid-19. This study used a cross sectional design on 138 confirmed Covid-19 patients at the Jakarta Islamic Hospital and used a questionnaire in the form of a google form with the analysis used, namely multiple logistic regression. The spirituality level scale adapts the daily spiritual experience scales (DSES), the spiritual care implementation scale adapts the Nursing Spiritual Care Therapeutics Scale (NSCTS) and social support adapts the Enrich Social Support Instrument (ESSI). This study shows the results of a significant relationship between the application of Spiritual Care with Spirituality Level (p=0.001) OR 3.919, and social support with spirituality level is very significant with a value (p=0.000/OR 4.167) while the dominant variable, namely social support has a high level of social support. high spirituality OR 3,580 times greater than having good social support compared to individuals who have low social support and the variable of implementing spiritual care OR 3,334 times higher than respondents having low spiritual care after being controlled by gender, age, religion, education and profession. This study recommends the need for nurses to increase spirituality values ​​in confirmed Covid-19 patients to be able to increase patient spirituality.